Analysis of Bioactive Components and Antioxidants of White Ear Mushroom Extract (Tremella fuciformis): Analisis Komponen Bioaktif dan Antioksidan Ekstrak Jamur Kuping Putih (Tremella fuciformis) - Adha, Muhammad Ari Risqi; Fiana podesta; Dwi fitriani; Suryadi (Universitas Muhammadiyah Sidoarjo, 2025)
Antioxidants are compounds that function to protect the body from damage caused by free radicals or reactive oxygen species (ROS). ROS are molecules formed through oxidation reactions in the body, either naturally or due to external factors such as pollution, UV radiation, and unhealthy dietary patterns. Purpose this study aimed to identify the bioactive components present in the extract of white ear fungus (Tremella fuciformis). Study details the research was conducted by the Department of Medical Laboratory Science and Biotechnology at Asia University between October and December 2024. Results flavonoids a concentration of 100 mg/ml yielded the highest antioxidant value in the white ear fungus extract. Phenolic content sample 1 exhibited the highest phenolic value in the white ear fungus extract compared to EDTA. DPPH at concentrations of 1, 5, and 10 mg/ml, the white ear fungus extract showed higher antioxidant activity than BHT. Reducing Power (RP) Similarly, at concentrations of 1, 5, and 10 mg/ml, the extract demonstrated stronger reducing power than BHT.